The key role of diabatic processes in modifying the upper-tropospheric wave guide: A North Atlantic case-study - Grams, Christian M.; Wernli, Heini; id_orcid:0 000-0001-9674-4837; Böttcher, Maxi; Campa, Jana; Corsmeier, Ulrich; Jones, Sarah C.; Keller, Julia H.; Lenz, Claus-Jürgen; Wiegand, Lars (Quarterly Journal of the Royal Meteorological Society, 2011)
ISSN:0035-9009 ISSN:1477-870X